2020
DOI: 10.5194/amt-2019-486
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Counting on Chemistry: Laboratory Evaluation of Seed Material-Dependent Detection Efficiencies of Ultrafine Condensation Particle Counters

Abstract: Condensation Particle Counters (CPCs) are crucial instruments for detecting sub-10 nm aerosol particles. Understanding the detection performance of a CPC requires thorough characterization under well-controlled laboratory conditions.Besides the size of the seed particles, chemical interactions between the working fluid and the seed particles also influence the activation efficiencies. However, common seed particle materials used for CPC characterizations are not chosen in respect of chemical interactions with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…As a sanity check of our approach, we first tested that butanol does not homogeneously nucleate under typical CPC conditions: a temperature of 10–25 °C and a butanol saturation ratio of 1–5. 10 , 69 In agreement with experiments, and with classical thermodynamic predictions, our modeling indicates negligible rates for homogeneous nucleation in these conditions.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As a sanity check of our approach, we first tested that butanol does not homogeneously nucleate under typical CPC conditions: a temperature of 10–25 °C and a butanol saturation ratio of 1–5. 10 , 69 In agreement with experiments, and with classical thermodynamic predictions, our modeling indicates negligible rates for homogeneous nucleation in these conditions.…”
Section: Discussionsupporting
confidence: 87%
“…The typical experimental nucleation temperature in CPCs ranges between 10 and 25 °C, and the butanol saturation ratio ranges from 1 to 5 (the butanol saturation vapor pressure at 25 °C is 919.2 Pa). 10 , 69 …”
Section: Resultsmentioning
confidence: 99%
“…This observation is consistent with a previous study (Hering et al, 2017). One possible explanation is that the chemical similarity between the seed particle material and the working fluid also affects the detection efficiency of the vWCPC 3789 (Wlasits et al, 2020).…”
Section: Effect Of Particle Chemical Composition On the Vwcpc 3789 Counting Efficiencysupporting
confidence: 93%
“…Thus, both settings are suitable for airborne operations up to 5.5 km with a 7 nm cut-off size. Note that the counting efficiency curve from TSI at 30 • was derived and fitted using an AS particle classified by a custommade different mobility analyzer (using an aerosol-to-sheath flow rate ratio of 1 : 100) under a near-sea-level pressure (Wlasits et al, 2020). As a result of operation over a much wider pressure range, the cut-off curve derived by this study is less sharp than for the TSI standard settings.…”
Section: Temperature Dependence Of the Vwcpc 3789 Cut-off Sizementioning
confidence: 88%
“…The general characteristic of a CPC is its detection efficiency curve: heterogeneous nucleation probability of the sample particles as a function of particle size. Typically, the most important parameter considered to determine heterogeneous nucleation probability is particle size (lower nucleation probability for smaller particles), while several studies have demonstrated that chemical interactions between the particles and the condensing vapor affect strongly the nucleation probability at constant particle size [12][13][14][15][16] . Uncertainty in the detection efficiency curve results in uncertainty in the measured nanoparticle concentrations, especially in systems where secondary particle formation takes place and this deteriorates the accuracy of the inferred aerosol dynamics.…”
Section: Introductionmentioning
confidence: 99%